2017
DOI: 10.1186/s40793-017-0267-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence of the white-rot fungus Irpex lacteus F17, a type strain of lignin degrader fungus

Abstract: Irpex lacteus, a cosmopolitan white-rot fungus, degrades lignin and lignin-derived aromatic compounds. In this study, we report the high-quality draft genome sequence of I. lacteus F17, isolated from a decaying hardwood tree in the vicinity of Hefei, China. The genome is 44,362,654 bp, with a GC content of 49.64% and a total of 10,391 predicted protein-coding genes. In addition, a total of 18 snRNA, 842 tRNA, 15 rRNA operons and 11,710 repetitive sequences were also identified. The genomic data provides insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Previous to our study, there was only one brief report on the genome sequence of an I. lacteus strain F17 [ 21 ]. In this study, we found that the genome of I. lacteus CD2 is 43.16 Mb, similar to but slightly smaller than that of formerly sequenced I. lacteus F17 (44.36 Mb).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous to our study, there was only one brief report on the genome sequence of an I. lacteus strain F17 [ 21 ]. In this study, we found that the genome of I. lacteus CD2 is 43.16 Mb, similar to but slightly smaller than that of formerly sequenced I. lacteus F17 (44.36 Mb).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the genome of I. lacteus CD2 is 43.16 Mb, similar to but slightly smaller than that of formerly sequenced I. lacteus F17 (44.36 Mb). Despite this similarity, however, I. lacteus CD2 encodes higher numbers of plant cell wall polysaccharide-degrading enzymes, with 182 GHs compared to 161 GHs in I. lacteus F17 [ 21 ]. In addition, I. lacteus CD2 does not have a laccase, but have 7 MnPs, 2 LiPs, and 4 DyPs, while I. lacteus F17 bears one laccase, one LiP, 13 MnPs but no DyP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 14 PODs enzymes include one LiP and 13 putative MnPs. Phylogenetic analysis based on 18S rRNA sequences showed that I. lacteus F17 was closely related to Ceriporiopsis subvermispora and Phanerochaete chrysosporium (Yao et al 2017 ). Interestingly, the genome of C. subvermispora also encodes 13 MnPs, whereas it has no genes encoding DyPs, similar to P. chrysosporium (Fernández-Fueyo et al 2012 ; Floudas et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%